SOCIAL INNOVATIONS AS A COMPONENT OF STATE SOCIAL POLICY - Volska, Olena (Pressing Problems of Public Administration, 2021)
The article considers the theoretical foundations of social innovations. The views of Ukrainian and foreign scientists on the nature of social innovations are given. Social innovation is: 1) the formation of new ideas, strategies, concepts, organizations, forms of organizations; 2) the process of change (new decisions), long-term social change of non-standard solutions to social problems, the development of structures, principles, practices; 3) changes in behavior, preferences of people, in the processes of influencing change, in regulation, policy, organizational structures and practices.It is proved that social innovations can have four definitions: a new solution to a social problem; innovative product, the use of which can affect the solution of a social problem; the way of spreading social innovation; uniqueness of social innovation. Examples of social innovations in the educational sphere are presented. The role of social innovations in the state social policy is determined.For the effective existence of social innovations, it is necessary to manage them. In this regard, it should be noted that when defining the concept of “management of social innovation” it is necessary to take into account many approaches to management (situational, factorial, etc. approaches). At the same time, social innovation should be considered as a component of social policy.1. Social innovation or innovative direction of social development is the process of implementation of social innovation in the state. This is a new social offer for a certain society, a new relationship between members of society. The basis of social innovation is not technical innovations, new methods of interaction between members of society, new criteria for their behavior, actions, state of the social environment.2. The introduction of social innovation involves a certain course of action based on the study of the features of social innovation as a component of social development. If we analyze the principle of action of the innovator in terms of social and technological innovation, it becomes clear that his actions will be determined by the specifics of social innovation as a component of social development.3. The specificity of social innovation as a component of social development is determined mainly by the fact that social innovation is not related to technology and technology. The main difference between social and technological innovations is in the new actions of the innovator, which are based on fundamentally new principles. The effect of technological innovation is primarily to increase productivity, the effect of social innovation is to achieve a social effect that is difficult to measure mathematically. This is primarily an increase in the level of satisfaction with the social benefits of society.4. Social innovations are accompanied by a number of actions of the subjects of innovation, namely:‑ the presence of positive social effects from social innovations that need to be shown to society;‑ elimination of negative effects from the implementation of social innovations;‑ analysis of the legal status of innovation through the definition of regulatory and legal support for the implementation of social innovation;‑ analysis of the emergence of disputes in society caused by the emergence of social innovations.